2018
DOI: 10.1177/1098612x18787910
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing practices of veterinarians in the treatment of chronic musculoskeletal pain in cats

Abstract: Objectives Despite the high prevalence and increasing awareness of chronic musculoskeletal pain in cats, approved treatment options are completely lacking in the USA, and few other options have sufficient safety and efficacy data. Knowledge of current prescribing practices should inform future research of putative therapies. We aimed to determine which drug and non-drug therapies were being used by general practitioners for the treatment of musculoskeletal pain in cats and to understand demographic influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
(37 reference statements)
1
27
0
Order By: Relevance
“…There are no approved medications for the treatment of chronic musculoskeletal pain in cats, and only a limited number of analgesic therapeutics with data about efficacy . Before the studies reported here, we surveyed veterinarians regarding pharmaceuticals and dietary supplements used for the alleviation of chronic pain in the cat . The most frequently prescribed treatment was gabapentin.…”
Section: Introductionmentioning
confidence: 99%
“…There are no approved medications for the treatment of chronic musculoskeletal pain in cats, and only a limited number of analgesic therapeutics with data about efficacy . Before the studies reported here, we surveyed veterinarians regarding pharmaceuticals and dietary supplements used for the alleviation of chronic pain in the cat . The most frequently prescribed treatment was gabapentin.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of different treatments are prescribed for feline chronic musculoskeletal disease, often with little evidence to back up their effectiveness. 66 A multimodal approach involving therapeutics, environmental management and other complementary therapies has been described to manage feline chronic pain, 67 and is the focus of the following discussion. The effect of obesity on musculoskeletal disease is discussed later in the prevention section; suffice to say at this point that controlled weight loss should be part of the treatment programme for obese cats with established musculoskeletal disease.…”
Section: Treatment Of Feline Musculoskeletal Impairment and Diseasementioning
confidence: 99%
“…67 Therapeutics A recent survey of predominantly North American veterinarians recorded the top five therapeutics prescribed for chronic musculoskeletal pain as being gabapentin (75%), joint supplement (67.8%), meloxicam (64%), opioids (62.6%) and fish oil (62.1%). 66 Therapeutics can be divided into analgesics and disease-modifying osteoarthritis (DMOA) drugs. Note that therapeutic licensing laws vary around the world.…”
Section: Treatment Of Feline Musculoskeletal Impairment and Diseasementioning
confidence: 99%
See 2 more Smart Citations